Advantages and disadvantages of self-determination support strategies for people with severe or profound intellectual and multiple disabilities: A Delphi study - Pála Björk Kúld; Noud Frielink; Carlo Schuengel; Petri Embregts (PLoS ONE, 2026)
Background The specific advantages and disadvantages of strategies that caregivers use to support self-determination in individuals with profound intellectual and multiple disabilities need to be known. This study explored consensus on advantages and disadvantages of support strategies from the perspective of users. Method A four-round Delphi study was conducted with 10 relatives and 13 professionals experienced in self-determination support. In Round 1, qualitative data were collected and thematically analysed. Subsequent rounds used Likert scales and participant feedback to explore consensus. Results Thematic analysis of Round 1 produced 79 themes, on which 72 consensus was reached across later rounds. On 63 themes, consensus was found across both groups. Users reported advantages such as mutual trust, reciprocal learning, and a more unified and efficient approaches to support self-determination. For individuals with disabilities, advantages included improved health, participation, and increased influence over their lives. However, disadvantages included preconditions that are often unmet in practice, such as consistent use of communication aids, sufficient time, and stable staffing. Conclusion Promoting self-determination in this population requires attention to their interactions with support networks and the quality of collaboration. Each support strategy has specific advantages and disadvantages that should be examined in light of the diversity within this population and their networks. Future research and practice could address identified barriers and build on advantages of support strategies by evaluating their applicability and relevance in individual cases.